Watershed Management Through Sustainable Development Concept: Literature Review - Bismihayati Bismihayati; Rahmi Putri Wirman; Lismomon Nata; Eni Kamal; Isril Berd; Abdul Razak (Science and Environmental Journal for Postgraduate, 2023)
Watersheds are a method of managing river water resources with the aim of preserving the viability of aquatic resources in the long term. One of the elements needed for management is how the current state of aquatic resources. Reduced flood swamp areas, sedimentation, decreased water discharge and water levels, and difficulties for some fish species to migrate are all effects of environmental modifications such as damming rivers for irrigation and hydroelectric power and changing the mass of water. In the middle and lower reaches of the river, the addition of anthropogenic materials from various industrial activities can have an impact on aquatic life, fish, and fishermen's catches. To ensure the future existence and survival of fish resources in river waters, it is necessary to manage resources, especially watersheds covering aquatic habitats with various species, as well as multi-species habitats. Watershed management considerations must include a variety of factors, including area/ecology, sector, scientific field, and stakeholders.